Analisis Konsumsi dan Perilaku Konsumen dalam Penggunaan Energi BBM untuk Kendaraan Bermotor di Surakarta - Roni Zakaria; Fakhrina Fahma; Sukma Hendra (Performa: Media Ilmiah Teknik Industri, 2010)
This study aims to determine people’s behavior in using the energy from fuel oil to know the amount of premium as well as private consumption index in Surakarta. This research was conducted in four stages. The first stage is to determine the sample. In determining the research sample, the method used is the area sampling and purposive sampling. While the number of respondents is determine by the formula Taro Yamane of 400 respondents. The second phase of preparing the questionnaire, all variables, attributes, and questions adapted from the model of consumer behavior Kotler (1997). The third stage cluster analysis and cluster profiling done to achieve the characteristics of Surakarta community. The last step in research is to calculate the index consumption Surakarta